Untangling the Web: The Impact of Social Media Miscommunication on Workplace Dynamics - Sudip Bhattacharya; G Jahnavi; Vanita Lal; Harminder Singh; Pratima Gupta; Saurabh Varshney (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Social media miscommunication refers to situations where messages, information, or intentions are not conveyed or understood as intended due to the nature of online communication platforms. This can happen for several reasons. Social media miscommunication can have several consequences in the workplace, potentially affecting individuals and the overall work environment. Tackling social media miscommunication requires a combination of awareness, effective communication strategies, and a commitment to maintaining a positive and respectful online presence. Last and most importantly, we need to keep in our mind that social media is a public forum, and our interactions can have a lasting impact. By approaching online communication with thoughtfulness and respect, we can help minimize the potential for miscommunication and maintain positive relationships in our digital ecosystem.